Terrestrial and airborne laser scanning and 2-D modelling for 3-D flood hazard maps in urban areas: new opportunities and perspectives. (January 2021) - Costabile, Pierfranco; Costanzo, Carmelina; De Lorenzo, Gianluca; De Santis, Rosa; Penna, Nadia; Macchione, Francesco
Abstract: The development of a shared understanding of current flood risk amongst stakeholders is one of the main goals of flood risk management. This priority suggests that stakeholders must understand the possible impacts on their property and assets, and measures they can take to mitigate the risk. Nowadays, flood maps are considered to be a potentially valuable tool for improving this understanding, but some drawbacks related to the use of flood maps for risk communication has been highlighted in the literature. An alternative and novel approach is provided by 3-D representations of flood inundation, so that supplementing flood maps with 3D visualization techniques is increasingly seen as a powerful tool with which to engage people with flood hazards. In this context, the detailed representation of the urban areas is important not only to set an accurate out-of-bank river model, essential for reliable simulations of flow dynamics inside the urban districts, but could be also a key element for the generation of realistic 3D views able to enhance risk perception and communication. In the framework described so far, 3D point cloud data provided by a terrestrial laser scanner could play an interesting role. Therefore, the main novelty introduced by this work is the combination of 2D flood simulations, 3D visual techniques and airborne/terrestrial laser scanning in order to develop new approaches for risk communication and perceptions. The potential of the methods developed here has been discussed in relation to a hypothetical flood event of the Crati river, flowing through the old city of Cosenza (South of Italy). Highlights: Development of 3-D hazard map technology for flood risk management. 2-D simulations results overlapped to vertical surfaces of the elements at-risk. Integration of TLS and airborne laser scanning for flood simulation and visualization. "human" meter composed of a silhouette of a man used as a visual indicator of water levels.